Health lipid indices of dry fermented sausages made of pork meat. Issue 1 (October 2021) - Parunovic, N; Trbovic, D; Ciric, J; Savic, R; Gogic, M; Betic, N; Radovic, C
Abstract: This research presents the results of a comparison assessment of the cholesterol content, fatty acid profile, and atherogenic (IA) and thrombogenic (IT) health lipid parameters of four dry fermented sausages produced from Mangalitsa and Swedish Landrace pork meat. The highest cholesterol level was found in Sremska sausage prepared from Landrace meat (64.92 mg/100g). Polyunsaturated fatty acid (PUFA) levels were considerably greater in Landrace meat sausages than in other kinds. The main cause of these variations was a higher overall n-6 PUFA concentration. The sausages made from Mangalitsa meat had the highest levels of monounsaturated fatty acid (MUFA) and unsaturated fatty acid (USFA). The highest saturated fatty acid (SFA) level was found in sausages prepared from Landrace meat. Fermented sausages made from Mangalitsa pork meat show better health lipid indices, atherogenic (IA), thrombogenic (IT), and PUFA/SFA ratios.